Structural Economics. (Taylor & Francis, 2004)
The interface of national accounting and economic analysis is something of a neglected area within economics. This important new book explains how national accounts can be used for economic modelling via input-output analysis - the main tool in the field. Structural Economics provides an accounting framework for the fundamental features of an economy - its technology, its endowments, and its pattern of consumption. The volume analyses economies in terms of output potential and other performance measures. Topics covered within these pages include axiomatic characterizations, solutions to dynamic models and unification of growth accounting and efficiency analysis. Thijs ten Raa's writings in this important area are presented here together for the first time. Students, academic economists and national accountants will find this book to be of great interest.